Voluntary Disclosure and Rating Disagreement among Credit Rating Agencies: Evidence from Korea. (27th June 2021) - Kim, Yujin; An, Jungin
Abstract: We examine the effect of voluntary disclosure on rating disagreement among credit rating agencies (CRAs). Previous empirical findings suggest that precise financial reporting decreases information risk and affects split ratings. However, no prior research has investigated the relationship between voluntary disclosure and split ratings, even though such disclosure can reduce information asymmetry. We find a negative relationship between voluntary disclosure and split ratings by CRAs. This study reveals voluntary disclosure that includes the manager's intentions (i.e., discretionary judgment) is a determinant of split ratings. In doing so the study contributes to the literature on the role of voluntary disclosure on CRAs.